Factors associated with unvoiced concerns of patients attributed to embarrassment, modesty or a fear of being judged - Hurtaud, Aline; Laurent, Clémence; Bouazzi, Leïla; Merland, Emilie Thery; Barbe, Coralie (BMC family practice, 2025)
It is important for patients to feel that they can address any topic during a consultation with a General Practitioner (GP), so that the care delivered is appropriate and relevant. This study aimed to investigate factors associated with unvoiced concerns of patients during a GP consultation, because of embarrassment, modesty and/or a fear of being judged. Cross-sectional, observational study between December 2023 and January 2024, using a ad hoc questionnaire completed by adult subjects who accepted to participate in the study. The factors associated with unvoiced concerns with a p-value < 0.20 by univariable analysis were included in a multivariable logistic regression model. In total, 2104 participants were included (mean age 43.7 ± 15.9 years; 73% women). Of these, 680 (32.3%, (95% CI, 30.3-34.3)) reported that they had leaved unvoiced concerns during the consultation due to embarrassment, modesty and/or a fear of being judged. The main motives for embarrassment, modesty and/or fear of being judged were: "sexual behavior, libido, perception of your gender, erectile dysfunction, vaginal dryness" (15% of respondents), and "psychological disorders, low mood, anxiety" (14%). Factors associated with a higher likelihood of unvoiced concerns were female sex (adjusted odds ratio (aOR) 1.5 [95% CI 1.2-1.9]; p = 0.0001) and third-level education (aOR 1.3 [95% CI 1.05-1.7]; p = 0.02). Conversely, heterosexuality (aOR 0.7 [95% CI 0.5-0.98]; p = 0.04) and a relationship of trust with the GP (aOR 0.6 [95% CI 0.5-0.7]; p < 0.0001) were associated with a lower likelihood of unvoiced concerns during GP consultation. Forty-seven percent of respondents said that hearing their GP reaffirm the secrecy of anything said during the consultation would have helped them to be more forthcoming, and 78% reported that they would have felt more at ease if the GP had addressed the difficult topic first. Simple tools that could be used during primary care consultations could help to address sensitive issues and create an environment where patients can more comfortably address all their health issues without discomfort.